Ocenjevanje natančnosti napovedi termohidravličnih programov - Prošek, Andrej (Strojniški vestnik, 2003)
Recently significant attention has been paid in code accuracy issues in predicting the dynamic responses of nuclear reactor systems. Though significant progress has been made, only a few reliable and general tools to quantify code accuracy are available. A new Stochastic Approximation Ratio Based Method (SARBM) was proposed for accuracy quantification. The objective of this study was to investigate and qualify the proposed method. The RELAP5/MOD3.2 thermal-hydraulic code calculations and the BETHSY experimental data were used in the process of qualifying the SARBM with a Fast Fourier Transform Based Method (FFTBM). The obtained results showed that the SARBM was able to satisfactorily predict the accuracy of the calculated transient trends when visually comparing plots and comparing the results with the results obtained by the qualified FFTBM. A new figure of merit for code accuracy, called the accuracy factor (AF), was proposed instead of the stohastic approximation ratio to make the total accuracy calculation with the SARBM more like the FFTBM approach. The accuracy results obtained for the selected BETHSY tests suggest combining the SARBM with the FFTBM for accuracy quantification rather than using it independently.
Keywords: BETHSY; natančnost izračunov; programi termohidravlični; NSA-SARBM; termohidravlični programi; natančnost; jedrski reaktorji